The self between : from Freud to the new social psychology of France - Webb, Eugene, 1938- (University of Washington Press, 1993)
An important emerging trend in contemporary French thought is challenging the basic assumptions of Freudian theory while seeking also to assimilate it in a new psychology that combines an awareness of the sociality of personhood with belief in a morally responsible self. "The events of the 1960s," writes Eugene Webb, including the loss of Algeria, the Soviet invasion of Czechoslovakia, and the American war in the former French colony of Indo-China, "effectively precluded any hope that might have been placed in the possibility that some grand movement of history led by some trustworthy agent or chosen people within it would result in a new and more promising world. The uprising of 1968 was the last desperate outburst of utopian expectations, and it ushered in a new introspectiveness that looked to psychoanalysis for explanations that philosophy and politics no longer seemed able to give." Thus people in France began to looks seriously to Freudianism, in the transformed version of Jacques Lacan, for a new way of understanding human relations and the relations between human beings and society. The movement in France is not specifically psychoanalytic but developed against such a background. Psychoanalytic thought acquired the kind of centrality in French intellectual life once associated with existentialism and Marxism and later with structuralism - a centrality it probably never possessed in the United States, even at the peak of its popularity. The current movement is a reassessment and rethinking of Freud's thought and influence, and it is a movement as yet almost unknown to the American public